Development of a new pump through modifying a conventional automotive spark plug. - hambali, A; Farid, Z.A; Najib, M (CSIR, 2010)
This study presents development of a new pump by modifying existing automotive spark plug, which is generally used for providing an electrode gap to produce an ignition in fuel-air mixture. Compressed air trapped between upper piston surface and spark plug was utilized by modifying spark plug design by implementing Pugh’s method.